Brand reputation as a fundamental element of international brand positioning for Mexican fashion brands (2022)
According to current business growth and brand positioning strategies, there are different ways in which companies and fashion brands manage to enter and / or position themselves in new international markets in order to achieve success. This article analyzes brand reputation as an element that influence brand positioning. The data collected from this investigation was generated through previously studied theories and scientific findings. The results obtained show that reputation, prestige and trust are multifactors that have greater relevance and weight in a brand’s positioning in an international market. For this article, the methodology will be a set of a qualitative descriptive and interpretive findings based on the objective of the research.